Revealing the knowledge concealment predictors in the Malaysian public sector - Osman, Suhaila; Hussin, Norhayati; Shahibi, Mohd Sazili (Faculty of Information Management, 2025)
Knowledge is considered a vital resource that affects the effectiveness and sustainability of any organization since it is a limited and scarce resource. Hence, possessing it can enhance and maintain an organization's competitive advantages. Organizations nowadays are mushrooming in managing their knowledge, as it is a vital strategic asset to their organizational success. Knowledge sharing is essential in knowledge management. Awkwardly, not sharing and concealing knowledge among employees in an organization has emerged as a significant impediment. Consequently, it could prohibit the organization's ongoing growth and survival. Knowledge concealment has clear detrimental repercussions on organizations, as it stifles creativity, obstructs teamwork and collaboration, and ultimately impacts organizational performance. Therefore, the aim of the study is to test the instrument on the knowledge concealment (KC) predictors among knowledge professionals in the Malaysian public sector. A quantitative research methodology was employed to collect data from knowledge professionals in five prominent ministries in Malaysia. The data were subsequently analyzed using the Statistical Package for Social Sciences (SPSS). The findings indicate that all variables in the study achieved a reliability score exceeding 0.7, thereby confirming their reliability. As a result, all items are deemed appropriate for inclusion in the research. These results contribute to the understanding of knowledge concealment and have a practical impact on the public sector for cultivating knowledge sharing and minimizing the concealment of knowledge among their employees.